Review of antibiotic resistance in China and its environment. (January 2018) - Qiao, Min; Ying, Guang-Guo; Singer, Andrew C.; Zhu, Yong-Guan
Abstract: Antibiotic resistance is a global health crisis linked to increased, and often unrestricted, antibiotic use in humans and animals. As one of the world's largest producers and consumers of antibiotics, China is witness to some of the most acute symptoms of this crisis. Antibiotics and antibiotic resistance genes (ARGs) are widely distributed in surface water, sewage treatment plant effluent, soils and animal wastes. The emergence and increased prevalence of ARGs in the clinic/hospitals, especially carbapenem-resistant gram negative bacteria, has raised the concern of public health officials. It is important to understand the current state of antibiotic use in China and its relationship to ARG prevalence and diversity in the environment. Here we review these relationships and their relevance to antimicrobial resistance (AMR) trends witnessed in the clinical setting. This review highlights the issues of enrichment and dissemination of ARGs in the environment, and also future needs in mitigating the spread of antibiotic resistance in the environment, particularly under the 'planetary health' perspective, i.e., the systems that sustain or threaten human health. Graphical abstract: Highlights: Antibiotics and ARGs are widely distributed in environment media in China. Antibiotic resistance varies geographically in China. Strategies to mitigate the spread of antibiotic resistance are suggested.